Pretty in punk: girls' gender resistance in a boys' subculture - Leblanc, Lauraine (Rutgers University Press, 1999)
Pretty in Punk combines autobiography, interviews, and sophisticated analysis to create the first insider's examination of the ways punk girls resist gender roles and create strong identities.Why would an articulate, intelligent, thoughtful young women shave off most of her hair, dye the remainder green, shape it into a mohawk, and glue it onto her head? What attracts girls to male-dominated youth subcultures like the punk movement? What role does the subculture play in their perceptions of themselves, and in their self-esteem? How do girls reconcile a subcultural identity that is deliberately coded “masculine” with the demands of femininity?Research has focused on the ways media and cultural messages victimize young women, but little attention has been paid to the ways they resist these messages. In Pretty in Punk, Lauraine Leblanc examines what happens when girls ignore these cultural messages, parody ideas of beauty, and refuse to play the games of teenage femininity. She explores the origins and development of the punk subculture, the processes by which girls decide to “go punk,” patterns of resistance to gender norms, and tactics girls use to deal with violence and harassment.Pretty in Punk takes readers into the lives of girls living on the margins of contemporary culture. Drawing on interviews with 40 girls and women between the ages of 14-37, Leblanc examines the lives of her subjects, illuminating their forms of rebellion and survival. Pretty in Punk lets readers hear the voices of these women as they describe the ways their constructions of femininity—from black lipstick to slamdancing—allow them to reject damaging cultural messages and build strong identities. The price they pay for resisting femininity can be steep—girls tell of parental rejection, school expulsion, institutionalization, and harassment. Leblanc illuminates punk girls' resistance to adversity, their triumphs over tough challenges, and their work to create individual identities in a masculine world.
https://www.rutgersuniversitypress.org/pretty-in-punk/9780813526515/
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; atlanta; culture populaire; entretien; ethnographie; genre; harcèlement sexuel; montréal; nouvelle-orléans; patriarcat; périodes historiques; régions géographiques; résistance; san francisco; stéréotypes de genre; systèmes d'oppressions; thématiques; violences

The flowers in your dustbin: Girls in the North American punk subcultures of the 1990s - Leblanc, Lauraine (Université Emory, 1997)
Girls in male-dominated youth subcultures confront ideologies of gender which remain largely invisible and often tacitly accepted in many women's everyday lives. Punk girls choose to construct their femininity within a highly male-dominated, "masculinist," context; girls are present in such youth subcultures, but the masculine definition of their norms problematizes their participation. Thus, punk girls struggle to accommodate female gender norms within subcultural identities which are deliberately coded as "masculine." Although young women in America encounter the norms of the female gender role on a daily basis, punk girls' negotiations between the norms of femininity and those of punk open these prescriptions to critical examination which they might not otherwise be accorded. In this dissertation, I explore accounts of punk girls' engagements with both mainstream and subcultural gender norms. In constructing this account of girls' lived experiences in the punk subculture, I rely primarily upon the phenomenology, or experiential narrative, of punk girls' everyday lives. I elicited these accounts within the context of conducting participant observation in the punk scenes of four North American cities (Atlanta, Montreal, New Orleans, and San Francisco) from 1993 to 1995, conducting ethnographic interviews with forty punk girls. In the following, I explore various facets of punk girls' engagements with gender norms, including punk girls' narratives of engagement with the subculture; the construction of punk as a discourse of masculinity; punk girls' stylistic, behavioral, and discursive reconstructions of femininity; punk girls' experiences of public harassment and sexual harassment, and their strategic responses to these. I argue that these girls use the punk subculture in order to carry out resistances to varied forms of gender oppression, thereby developing stronger self-concepts in the face of adversity.
https://search.libraries.emory.edu/catalog/990005217790302486
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; atlanta; discipline; ethnographie; genre; harcèlement sexuel; masculinisme; montréal; mémoires/thèses; nouvelle-orléans; patriarcat; philosophie; périodes historiques; régions géographiques; résistance; san francisco; sciences humaines; systèmes d'oppressions; thématiques; violences

Only words - MacKinnon, Catharine A. (Harvard University Press, 1993)
When is rape not a crime? When it's pornography–or so First Amendment law seems to say: in film, a rape becomes "free speech." Pornography, Catharine MacKinnon contends, is neither speech nor free. Pornography, racial and sexual harassment, and hate speech are acts of intimidation, subordination, terrorism, and discrimination, and should be legally treated as such. Only Words is a powerful indictment of a legal system at odds with itself, its First Amendment promoting the very inequalities its Fourteenth Amendment is supposed to end. In the bold and compelling style that has made her one of our most provocative legal critics, MacKinnon depicts a society caught in a vicious hypocrisy. Words that offer bribes or fix prices or segregate facilities are treated by law as acts, but words and pictures that victimize and target on the basis of race and sex are not. Pornography–an act of sexual domination reproduced in the viewing–is protected by law in the name of "the free and open exchange of ideas." But the proper concern of law, MacKinnon says, is not what speech says, but what it does. What the "speech" of pornography and of racial and sexual harassment and hate propaganda does is promote and enact the power of one social group over another. Cutting with surgical deftness through cases of harassment in the workplace and on college campuses, through First Amendment cases involving Nazis, Klansmen, and pornographers, MacKinnon shows that as long as discriminatory practices are protected as free speech, equality will be only a word.
Section: 152 p. ; 19 cm
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; cours; discipline; droit; histoire et politique; patriarcat; premier cycle; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sciences sociales; sex1911; sexisme; sexualité; sofia; systèmes d'oppressions; thématiques; violences; états-unis; études de genres

Mapping the margins: Intersectionality, identity politics, and violence against women of color - Crenshaw, Kimberlé William (Stanford Law Review, 1991)
Contemporary feminist and antiracist discourses have failed to consider the intersections of racism and patriarchy. To overcome this difficulty, an original approach is suggested here: that of intersectionality. In the first part, the paper discusses structural intersectionality, the ways in which the location of women of color at the intersection of race and gender makes their real experience of domestic violence, rape, and remedial reform qualitatively different from that of white women. The focus is shifted in the second part to political intersectionality, with the analysis of how both feminist and antiracist politics have functioned in tandem to marginalize the issue of violence against women of color. Finally, the implications of the intersectional approach are addressed within the broader scope of contemporary identity politics.
Keywords: 1900-1999; OFDIG; afro-féminisme; amériques; antiracisme; approches et analyses; cours; cycles supérieurs; fem9000; femmes* afro-américaines; féminismes noirs; incontournable; intersectionnalité; militance; patriarcat; périodes historiques; racisme; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; violences; violences contre les femmes*; violences raciales; états-unis

Homeplace : a site of resistance dans Yearning: race, gender, and cultural politics - Hooks, Bell (Yearning: race, gender, and cultural politics, 1990)
bell hooks crosses boundaries in major debates on postmodern theory, cultural criticism, and the politics of race and gender. She warns that “discourse” about “difference” is dangerously detachable from more essential struggles.
Section: 236 p
Keywords: 1900-1999; 1980-1989; afro-féminisme; amérique du nord; amériques; antiracisme; approches et analyses; cours; discipline; féminisme afroaméricain; histoire et politique; patriarcat; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; soc3113; sociologie; systèmes d'oppressions; thématiques; violences; états-unis

Microcosm - Duffy, Maureen (Virago, 1989)
À la House of Shades, Matt, un philosophe de bar, tente de donner un sens aux vies disparates qui se croisent ici : de Judy qui réserve elle-même et ses plus beaux atouts pour un amant du samedi soir, de Steve le professeur de gym qui redoute une chance. rencontre avec une élève dans cet environnement crépusculaire, et avec Matt elle-même, qui a besoin de ces échanges indirects malgré la sécurité de sa relation avec Rae et son sentiment que ce sanctuaire lesbien est aussi une prison, renforçant la culpabilité et l'éloignement des rues de la ville au-delà. Ailleurs, il y a des femmes comme Marie, prisonnière d'un mariage non désiré et incapable d'admettre sa sexualité, et Cathy, pour qui découvrir qu'elle n'est pas « la seule au monde » est une affirmation de son existence. Avec sa structure et son style innovants, reflétant parfaitement les voix et les expériences des femmes contraintes par la société à vivre en marge, The Microcosm reste aussi puissant aujourd'hui que lors de sa première publication en 1966.
Première édition: 1966
Keywords: 1900-1999; 1960-1969; approches et analyses; hétérosexisme; identités LGBTQIA2+; patriarcat; personnes lesbiennes; périodes historiques; roman; sexualité; systèmes d'oppressions; thématiques; travail; violences

Jeunes femmes et « contre-culture » au Québec - Lamont, Ève (Les Cahiers du Grif, 1986)
https://www.persee.fr/doc/grif_0770-6081_1986_num_34_1_1698
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; patriarcat; périodes historiques; québec; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; violences

The death of nature: Women, ecology and the scientific revolution - Merchant, Carolyn (New York : Harper & Row, 1983)
Un examen de la révolution scientifique qui montre comment la vision mécaniste du monde de la science moderne a sanctionné l'exploitation de la nature, l'expansion commerciale sans retenue et un nouvel ordre socio-économique qui subordonne les femmes.
Keywords: approches et analyses; capitalisme; discipline; environnement; histoire; histoire des sciences; histoire et politique; incontournable; patriarcat; philosophie; progrès; projet charge mentale; santé; sciences humaines; systèmes d'oppressions; thématiques; violences; violences envers la nature; violences envers les femmes*; écoféminisme

Pornography: Men possessing women - Dworkin, Andrea (Putnam, 1981)
Pornography: Men Possessing Women est un livre de 1981 sur la pornographie dans lequel Andrea Dworkin analyse (et cite abondamment des exemples tirés de) la pornographie contemporaine et historique comme une industrie qui déteste et déshumanise les femmes. Dworkin soutient que l'industrie est impliquée dans la violence contre les femmes, à la fois dans sa production (à travers l'abus des femmes qui y jouent le rôle principal) et dans les conséquences sociales de sa consommation en encourageant les hommes à érotiser la domination, l'humiliation et l'abus. des femmes.
https://www.feministes-radicales.org/wp-content/uploads/2010/11/Andrea-DWORKIN-Pornography-Men-Possessing-Women-1981.pdf
Keywords: approches et analyses; corps; cours; cycles supérieurs; fem9000; patriarcat; premier cycle; ressource en ligne; sex1911; sexisme; systèmes d'oppressions; thématiques; violences

La Mère des herbes - Marchessault, Jovette (Quinze, 1980)
Second volet d'une trilogie romanesque intitulée Comme une enfant de la terre. Le premier volet (Le crachat solaire) a obtenu le Prix France-Québec 1976. Imprécations et transgressions. Un roman "autobiographique et épique", violent, incantatoire, poétique, révolté. L'héroïne est une petite Québécoise élevée dans une culture de violence (mâle et chrétienne) et d'intimidation, qui raconte ses expériences et ses intuitions, les instants de bonheur passés avec sa grand-mère autochtone, pianiste et guérisseuse, etc.
Keywords: amériques; approches et analyses; autobiographie; enfance; littérature québécoise; patriarcat; québec; roman; régions géographiques; systèmes d'oppressions; thématiques; violences; écriture des femmes*

Pratique du pouvoir et idée de Nature (1) : l’appropriation des femmes - Guillaumin, Colette (Nouvelles Questions Féministes, 1978)
Dans les rapports de genre, le fait que les hommes puissent s'assurer la force de travail des femmes sans contrepartie mesurable (en temps, en argent, etc.) montre que la nature de la relation est différente de celle de la vente classique du travail. Comme dans l'esclavage et le servage, il y a appropriation directe de la base matérielle – corporelle – de l'individu. Cette appropriation se manifeste, dans la forme matrimoniale de cette relation, par le fait que le travail n'est pas évalué, par l'appropriation des produits – parmi lesquels les enfants –, par le droit illimité d'utiliser le corps de l'épouse. Elle s'exprime par la nature de certaines tâches : la responsabilité, par exemple, des besoins corporels du dominant et de ses dépendants. Ces tâches sont empiriquement associées à l'appropriation corporelle (du dominé), par exemple dans l'esclavage. La relation sociale que l'on pourrait appeler « sexage » est à la fois collective (appropriation collective des femmes par les hommes) et privée (comme dans le mariage, qu'il soit légal ou de droit commun).
https://prod-cdn.atria.nl/wp-content/uploads/sites/2/2019/01/25131247/ANEF-1978065800001.pdf
Keywords: approches et analyses; care; discipline; domination masculine; féminisme matérialiste; patriarcat; rapports sociaux de sexe; ressource en ligne; sciences humaines; sexisme; sexualité; sociologie; systèmes d'oppressions; thématiques; travail; violences

Ainsi soit-elle - Groult, Benoîte (Librairie Générale Française, 1977)
En tête des espèces recensées sur notre globe s'inscrit l'humaine, bien sûr, incarnée dans l'homo sapiens. De nos jours, un chœur de voix de plus en plus fortes proclame qu'il n'est pas l'unique représentant présentable de l’espèce, que sa compagne la mulier (la femme) est sapiens aussi et a le droit d'occuper une place au soleil égale à la sienne, même si par tradition il la considère comme sa « moitié ». « La tradition, voilà le mot clef qui a servi à justifier depuis des siècles la condition des femmes; une tradition établie par les hommes et renforcée par des lois, également conçues par les hommes. Il était fatal que le jour où les femmes prendraient conscience de cette injustice, elles se révolteraient contre le sort qui leur est fait, un sort que la vie quotidienne masque encore à quelques-unes d'entre elles, privilégiées, aveugles ou Ignorantes. » Le livre de Benoîte Groult vient à point dessiller les yeux de celles-ci ou renseigner celles-là et les hommes également afin que tous comprennent que le féminisme n'est pas une névrose ou une le mode mais une nécessité vitale, qu'« il faut enfin guérir d'être femme. Non pas d'être née femme, mais d'avoir été élevée femme dans un univers d'hommes », comme l'écrit Benoîte Groult, avant de rappeler les conditionnements de toutes sortes imposés aux femmes depuis les temps bibliques pour le seul confort et le seul bénéfice de l'autre sexe. Une documentation solide, un humour parfois corrosif mais sou-vent réjouissant font de cet exposé sobre et objectif un des meilleurs ouvrages sur la question féminine
Keywords: 1900-1999; approches et analyses; care; cours; discours dominant; europe; fem1000; france; militance; patriarcat; premier cycle; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; violences; violences sexistes et sexuelles; émotions

Violence et contrôle social des femmes - Hanmer, Jalna (Questions Féministes, 1977)
https://www.jstor.org/stable/40619104
Keywords: 1900-1999; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem7000; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; sciences humaines; sociologie; systèmes d'oppressions; thématiques; violences